Consumer Preferences for Olive-Oil Attributes: A Review of the Empirical Literature Using a Conjoint Approach - Jiménez-Guerrero, José Felipe; Gázquez-Abad, Juan Carlos; Mondéjar-Jiménez2, Juan Antonio; Huertas-García, Rubén (IntechOpen, 2012)
None